Causal associations between modifiable risk factors and pancreatitis: A comprehensive Mendelian randomization study - Mao, Xiaotong; Mao, Shenghan; Sun, Hongxin; Huang, Fuquan; Wang, Yuanchen; Zhang, Deyu; Wang, Qiwen; Li, Zhaoshen; Zou, Wenbin; Liao, Zhuan (Frontiers in Immunology, 2023)
Background: The pathogenesis of pancreatitis involves diverse environmental risk factors, some of which have not yet been clearly elucidated. This study systematically investigated the causal effects of genetically predicted modifiable risk factors on pancreatitis using the Mendelian randomization (MR) approach. Methods: Genetic variants associated with 30 exposure factors were obtained from genome-wide association studies. Summary-level statistical data for acute pancreatitis (AP), chronic pancreatitis (CP), alcohol-induced AP (AAP) and alcohol-induced CP (ACP) were obtained from FinnGen consortia. Univariable and multivariable MR analyses were performed to identify causal risk factors for pancreatitis. Results: Genetic predisposition to smoking (OR=1.314, P=0.021), cholelithiasis (OR=1.365, P=1.307E-19) and inflammatory bowel disease (IBD) (OR=1.063, P=0.008) as well as higher triglycerides (OR=1.189, P=0.016), body mass index (BMI) (OR=1.335, P=3.077E-04), whole body fat mass (OR=1.291, P=0.004) and waist circumference (OR=1.466, P=0.011) were associated with increased risk of AP. The effect of obesity traits on AP was attenuated after correcting for cholelithiasis. Genetically-driven smoking (OR=1.595, P=0.005), alcohol consumption (OR=3.142, P=0.020), cholelithiasis (OR=1.180, P=0.001), autoimmune diseases (OR=1.123, P=0.008), IBD (OR=1.066, P=0.042), type 2 diabetes (OR=1.121, P=0.029), and higher serum calcium (OR=1.933, P=0.018), triglycerides (OR=1.222, P=0.021) and waist-to-hip ratio (OR=1.632, P=0.023) increased the risk of CP. Cholelithiasis, triglycerides and the waist-to-hip ratio remained significant predictors in the multivariable MR. Genetically predicted alcohol drinking was associated with increased risk of AAP (OR=15.045, P=0.001) and ACP (OR=6.042, P=0.014). After adjustment of alcohol drinking, genetic liability to IBD had a similar significant causal effect on AAP (OR=1.137, P=0.049), while testosterone (OR=0.270, P=0.002) and triglyceride (OR=1.610, P=0.001) and hip circumference (OR=0.648, P=0.040) were significantly associated with ACP. Genetically predicted higher education and household income levels could lower the risk of pancreatitis. Conclusions: This MR study provides evidence of complex causal associations between modifiable risk factors and pancreatitis. These findings provide new insights into potential therapeutic and prevention strategies.